1989
DOI: 10.1111/j.1471-4159.1989.tb07357.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Novel Serotonin Receptor Subtype (5‐HT1E) in Human Brain: Interaction with a GTP‐Binding Protein

Abstract: [3H]Serotonin (5-hydroxytryptamine, [3H]5-HT) was used as a radioligand probe of brain 5-HT receptors in homogenates of human cortical tissue. Two binding sites were detected in the presence of 1 microM pindolol (to block 5-HT1A and 5-HT1B receptors), and 100 nM mesulergine (to block 5-HT1C and 5-HT2 receptors). One of these sites demonstrated high affinity for 5-carboxyamidotryptamine (5-CT) and ergotamine, consistent with the known pharmacology of the 5-HT1D receptor; the second site demonstrated low affinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(88 citation statements)
references
References 30 publications
4
84
0
Order By: Relevance
“…(Pedigo et al, 1981;Heuring & Peroutka, 1987 Hoyer et al, 1985;Heuring & Peroutka, 1987;Leonhardt et al, 1989), which increases the complexity of binding curves and data analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(Pedigo et al, 1981;Heuring & Peroutka, 1987 Hoyer et al, 1985;Heuring & Peroutka, 1987;Leonhardt et al, 1989), which increases the complexity of binding curves and data analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The hypothesis that 5-HTIB receptors represent the species homologue of the 5-HTID receptor (Adham et al, 1992) (Leonhardt et al, 1989;Weisberg & Teitler, 1992;Beer et al, 1992 (Hamblin & Metcalf, 1991) and a 5-HTIE receptor (McAllister et al, 1992). Also as predicted on the basis of radioligand binding assays performed in brain membrane homogenates from numerous mammalian species (Leonhardt et al, 1989;Beer et al, 1992), the human 5-HTIE receptor as opposed to the 5-HTID receptor, has been shown to have a low affinity for 5-CT, ergotamine and sumatriptan. Recently, based upon sequence homology, another new member of the 5-HT, receptor family has been described (Adham et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, studies using radioligand binding assays and molecular biology techniques have revealed that at least four types of 5-HT receptors exist in the vertebrate CNS, i.e., 5-HT1, 5-HT2, 5-HT3 and 5-HT4 (Peroutka & Snyder, 1979;Kilpatrick et al, 1987;Bockaert et al, 1992). The 5-HT, receptor site has been further divided into six distinct receptor subtypes: 5-HTIA, 5-HTIB, 5-HTc, 5-HTID, 5-HTlE and 5-HTIF (Pedigo et al, 1981;Pazos et al, 1985;Heuring & Peroutka, 1987;Leonhardt et al, 1989;Adham et al, 1993). The 5-HTc receptor shares homology with the 5-HT2 receptor subtype and has recently been termed the 5-HT2c receptor while the 5-HT2 receptor has been renamed the 5-HT2A receptor (Humphrey et al, 1993).…”
Section: Introductionmentioning
confidence: 99%